Consignment Income Recognition and Measurement in Indonesia Retail Companies - Zharunisa Zharunisa; Priandaru Wahyu Hutomo; Amrie Firmansyah (STKIP Singkawang, 2018)
This study aims to review the consignment income recognition and measurement from the consignee. Up to now, there is no specific Indonesia Statement of Financial Accounting Standards (hereinafter referred to as PSAK) that regulates the recognition, measurement, and disclosure of consignment revenues. The PSAK used in this study refers to PSAK 23, 2017 on Corporate Revenues.The research method used in this research is qualitative descriptive by comparing data obtained from direct observations in a company with theories and financial accounting standards related to consignment income. The population used in this study is the financial statements of 2017 from the retail sub-sector companies listed on the Indonesia Stock Exchange (IDX). Based on the examination of 93 companies regarding consignment transaction information, this study obtained a final sample of 10 companies. This paper analyzes the application in the consignment income recognition and measurement in retail companies to further examine its suitability with revenue recognition by PSAK 23, 2017.This study finds that the retail sub-sector companies have some similarities in recording consignment revenues and have obediently made disclosures related to consignment sales revenue following PSAK 23, 2017 even though there was no specific PSAK regulating consignment.